The Role of Multi Track Diplomacy In Resolving Intolerance Among Indonesian Citizen (Study case Blashpemy Againts Islam by Basuki T. Purnama) - Mujiono, Dadang Ilham Kurniawan; Kencana, Singgih Daru; Prahara, Nur Fitriana Pereda (Interdependence Journal of International Studies, 2020)
Over the period to today society, a religious dispute is remained to occur in many states in the world, and those conflicts trigger horrible situation and possible to destroy the unity of a nation in the world. Furthermore, one of religious conflict occurs in Indonesia, especially after one of Indonesia politician Basuki T. Purnama also known as Ahok trigger national tension since his controversial speech at Pulau Pramuka of Kepualauan Seribu which mentioning about Qur’an Surah Al-Maidah verse 51 viral via social media. In terms of methodology, this scientific paper categorized as descriptive where the author describes the case and find out the source of the problem, impact to the Unity of Indonesia along with the effort of Indonesia Government for the sake of alleviating the problem. In relation to the source of data, this research classified as secondary data through conducting literature review and number of relevant sources such as journals and scientific papers cited to this paper. The conceptual framework of the research, in addition, is the concept of Tolerance, that the author will describe how Indonesia Government mitigate the problem toward implementing Tri-Unity and inter-faith dialogue. The result shows that the blasphemy against Islam by Ahok has caused an unstable situation and the rates of intolerance activities has significantly increased over time, especially after Ahok’s case. For this reason, the government of Indonesia decided to coordinate with all component of Indonesia citizen (religious, politician, police and army as well as a citizen) for the sake of preserve Indonesia unity under the framework of Unitary of the Republic Indonesia and Bhineka Tunggal Ika.